ALOS PRISM (AW3D05 STANDARD) and Sentinel-1: Evaluation of New Sources of Digital Elevations Models - Marotta, Giuliano Sant'Anna; Cicerelli, Rejane Ennes; Barbosa, Vitória Rodrigues Ferreira; Almeida, Tati de; Rodrigues, Suzan Waleska Pequeno (Revista Brasileira de Geografia Física, 2020)
Digital Elevation Models (DEM) have many uses and many characteristics that influence choice of model to be used depending on the scale and research objectives. With the advancement of technology, new DEMs have emerged, as well as credible and widespread products such as Sentinel-1 and Advanced Land Observations Satellite World 3D (ALOS AW3D), each with distinct configurations. The height quality evaluation was performed based on Cartographic Accuracy Standard (PEC-PCD) analysis, tendency tests and examination of a profile in a region with rugged relief. A comparison was made with traditional DEM such as SRTM, ALOS PRISM, ALOS PALSAR and ASTER GDEM 2 with new DEMs AW3D Standard and MDS generate from Sentinel-1. The news DEMs have been classified as PEC B at regional scales (1:50,000). The AW3D Standard offers the best result, being rated PEC C for 1:25,000 scale. Another aspect should also be considered, the standard AW3D is capable of presenting more details on the terrain surface, while the DEM from Sentinel-1 SAR data presents a smoothed pattern. Sentinel-1 compared with products of the same spatial resolution, it is concluded that SRTM, ALOS PRISM, ALOS PALSAR products presented superior altimetric accuracy. While that the AW3D, despite the improvement in spatial resolution and altimetric accuracy remained in the same category as the PEC-PCD of the others.